PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA FIRMA BINTANG TIMUR DI SAWANGAN DEPOK - Siti Fitriani; Endang Suprapti (Jurnal Menara, 2025)
This study aims to determine the influence of leadership style and organizational culture on employee performance, both partially and simultaneously, at Bintang Timur Firm in Sawangan Depok. The study used a quantitative method with a saturated sample technique of 63 employees. Data analysis was carried out through instrument testing, classical assumption tests, simple and multiple linear regressions, correlation coefficients, determination coefficients, and hypothesis tests (t-test and F-test). The results showed that leadership style had a significant positive effect on employee performance with the regression equation Y = 8.332 + 0.840X1. The correlation coefficient of 0.877 indicates a very strong relationship, and the determination coefficient of 76.9% means that performance is influenced by leadership style by 76.9%. This is reinforced by the t-test with a calculated t value of 10.103> t table 2.000 and a significance of 0.000 <0.05. Organizational culture also has a significant positive effect on performance, shown by the regression equation Y = 4.742 + 0.936X2. The correlation coefficient of 0.906 indicates a very strong relationship, with a determination of 82%, meaning that performance is influenced by organizational culture by 82%. The t-test proves a value of 12,193 > 2,000 with a significance of 0.000 < 0.05. Simultaneously, leadership style and organizational culture have a significant effect on employee performance with a multiple regression equation of Y = 0.927 + 0.454X1 + 0.591X2. The correlation coefficient of 0.966 indicates a very strong relationship, while a determination of 93.4% means that performance is influenced by both variables by 93.4%. The F-test produces a value of 421,217 > 2.76 with a significance of 0.000 < 0.05. Thus, Ho is rejected and Ha is accepted.